The Effectiveness of Using Interactive Game Methods in the Mental and Physical Development of Preschool Children - Ismailova Sabina Erkin qizi; Ismailova Gulmira Erkin qizi (Zien Journals, 2022)
This article discusses the changes in the lives of young children in preschool education and the role of interactive games in their development.
Keywords: Preschool education; real; pedagogical and psychological research